Implementasi Program ROSELA dalam Meningkatkan Kualitas Hidup Lansia di Kabupaten Lamongan - Sigit Putra Agung Winata; Sjafiatul Mardliyah (J+PLUS UNESA, 2026)
The increase in the elderly population as a consequence of demographic transition necessitates the development of social policies that can ensure sustainable welfare. The ROSELA Program in Lamongan Regency serves as an intervention that integrates social protection with family economic empowerment. This study aims to examine the implementation of the ROSELA Program in improving the quality of life of the elderly in Lamongan Regency, as well as to analyze the supporting and inhibiting factors in its implementation. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving various stakeholders, including elderly beneficiaries, program implementers, local government officials, and beneficiaries’ families. The collected data were analyzed descriptively through stages of data reduction, data presentation, and systematic conclusion drawing to obtain a comprehensive understanding of the program implementation in the field. The findings indicate that the implementation of the ROSELA Program is carried out through a combination of direct social assistance to the elderly and efforts to strengthen the economic capacity of families as the primary support system for their welfare. Supporting factors of the program include cross-sector collaboration, active involvement of local government at the village level, and the participation of neighborhood units (RT/RW) in the data collection and beneficiary selection processes. Meanwhile, inhibiting factors include limited regional budget capacity, dynamic changes in beneficiary data, and technical challenges in field monitoring activities. Keywords: policy implementation, social development, social welfare, elderly.